2022
DOI: 10.1261/rna.079404.122
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the epitranscriptome by native RNA sequencing

Abstract: Chemical RNA modifications, collectively referred to as the ‘epitranscriptome’, are essential players in fine-tuning gene expression. Our ability to analyze RNA modifications has improved rapidly in recent years, largely due to the advent of high throughput sequencing methodologies, which typically consist of coupling modification-specific reagents, such as antibodies or enzymes, to next-generation sequencing. Recently, it also became possible to map RNA modifications directly by sequencing native RNAs using n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 162 publications
0
37
1
Order By: Relevance
“…To reveal characteristics of the rRNA processing pathway(s) in archaea we applied long-read nanopore sequencing to the total RNA of three archaeal model organisms, namely the Euryarchaea Haloferax volcanii and Pyrococcus furiosus and the Crenarchaeon Sulfolobus acidocaldarius (Figure 1A). For maturation stage classification, amplification-free direct cDNA sequencing was performed in a poly(A)-independent way using a custom 3’-adapter to improve the accuracy of 3’ end detection (Figure 1B,C,D), while direct RNA sequencing was used for stage-dependent base modification analysis (Figure 1B,E) (14, 21, 34). Note that we previously showed that artificial polyadenylation of prokaryotic RNAs impairs the accuracy of 3’ detection (14).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To reveal characteristics of the rRNA processing pathway(s) in archaea we applied long-read nanopore sequencing to the total RNA of three archaeal model organisms, namely the Euryarchaea Haloferax volcanii and Pyrococcus furiosus and the Crenarchaeon Sulfolobus acidocaldarius (Figure 1A). For maturation stage classification, amplification-free direct cDNA sequencing was performed in a poly(A)-independent way using a custom 3’-adapter to improve the accuracy of 3’ end detection (Figure 1B,C,D), while direct RNA sequencing was used for stage-dependent base modification analysis (Figure 1B,E) (14, 21, 34). Note that we previously showed that artificial polyadenylation of prokaryotic RNAs impairs the accuracy of 3’ detection (14).…”
Section: Resultsmentioning
confidence: 99%
“…Cleavage sites at the bulge-helix-bulge are indicated by orange triangles and dashed vertical lines. E, RNA base modifications can lead to deviations in the recorded current intensities from the expected signal and/or to systematic basecalling errors, which can be used to detect RNA modifications (34).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these advances, several major obstacles remain to detecting a broad repertoire of nucleic acid modifications by machine learning approaches. Developing robust algorithms for modified base calling requires DNA and RNA training sets that contain modified nucleotides in all possible sequence contexts, a non-trivial endeavor for nucleic acid modifications that cannot be readily generated by chemical synthesis or enzymatic modification ( Begik et al, 2022 ). This includes the majority of the 170+ endogenous modifications present on RNA molecules ( Boccaletto et al, 2022 ).…”
Section: Bioinformatic Strategies For De Novo Modi...mentioning
confidence: 99%